Maximum Labial Frenektomi Using The Two-Clamps Technique In Fixed Orthodontic Patients: A Case Report - Yoseph Saferius Kanisius Ani; Firman Salam; Hasanuddin Thahir (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: The frenulum is a fold of mucous membranes that attaches the lips to the alveolar mucosa, gingiva, and underlying periosteum. The high and large frenulum attachment between the maxillary incisors can cause aesthetic problems in orthodontic results. Therefore, surgical removal of the frenulum is necessary to prevent a recurrence, gingival recession, difficulty in oral hygiene, interference with labial movement, and esthetic or orthodontic requirements. History and Clinical Findings: A 20-year-old woman with fixed orthodontic wear one month ago was referred from the orthodontics department because there was a high and large frenulum attachment between the maxillary incisors. Clinical examination obtained diastema on teeth 11, 12, 13 and 21, 22, 23, 31, 32, 33 and 41, 42, 43, with Angle Class I occlusion. There were no abnormalities in the oral mucosa and the patient had no history of systemic disease. Case Management: Management of frenectomy using clamps and a scalpel with the two clamps technique method. Discussion: Frenectomy is the frenulum-cutting procedure with the aim of improving esthetics due to central diastema. A frenectomy is performed conventionally with a scalpel using a two-clamp technique to remove the muscle fibers that connect the orbicularis oris to the palatine papillae, with excision covering the interdental tissue, palatine papillae, and frenulum. Concussion: Closure of the diastema between the maxillary incisors with a prominent frenulum is more predictable with frenectomy and concomitant orthodontic treatment than with frenectomy alone.